Diagnóstico de la osteoartritis en el equino. Relación entre signos clínicos y biomarcadores proinflamatorios en el líquido sinovial - Perrone, Gustavo Mario (2016)
Degenerative joint disease or osteoarthritis (OA) is the most frequent disease in the horse and it is considered, internationally, as responsible for 60% of the sport horse lameness problems.In sports in which the horse life is prolonged, in addition to the changes of age chronic forms of the disease due to the failure of the cartilage joint to withstand cyclical sport trauma are frequently observed. In young animals, the repeated injuries can lead to the removal of the horse from competition, even at relatively early ages.\nThis repeated trauma, product of the sports competition, produces synovitis and capsulitis, damage to collateral ligaments, intra articular fractures and subchondral bone lesions. These processes lead to the clinical manifestations of OA, either acute or chronic with recurrent relapses characteristic of this disease.OA can be defined as a progressive, degenerative disease that is characterized by a loss of cartilage joint, subchondral bone eburnification and inflammation of the synovial membrane and synovial fluid increased. The resulting inflammatory processes produce proinflammatory cytokines that activate matrix metalloproteinases (MMPs) which in turn feedback the process by destruction of cartilage extracellular matrix (CEM).The diagnosis of OA is based on the clinical semiology and complementary methods. In the clinical diagnosis is of fundamental importance the standardized description of the symptoms of a disease, as well as signs of their evolution or progression in time to unify the criteria of diagnosis among professionals, to determine the type and severity of the disease, to define guidelines for the inclusion of patients in research trials, to characterize the animal models used in the research of diseases affecting human beings and finally, for statistically quantify the progress, successes and failures in the treatments.\nSeveral scores for evaluating OA developed by organizations such as the International Knee Documentation Committee (IKDC) and the International Cartilage Repair Society (ICRS) are described in human medicine. These scores include subjective assessments, with participation of the patient, objective, carried out by clinical and complementary examinations, and scores\nthat include both types of evaluations. In veterinary medicine, the collaboration of the patient in the anamnesis is null and that obtained from the person in charge of the animal can be incomplete or unreliable. Therefore the preparation of scores is fundamentally based on the observations made by the veterinarian.\nOur working group developed a clinical score for evaluating the tarsus astragalin joint comprising the AAEP modified score, manoeuvres of palpation pressure and forced flexions, observation of the profile joint and the degree of hydrarthrosis and physical characteristics of synovial fluid.The traditional analysis of synovial fluid included evaluation of enzymes (AST, LDH, FA), total protein, urea and the white blood cell count. Following the discovery of new biomarkers (BMs) and its effectors in the inflammatory cascade, their application in early diagnosis of OA, the development of new treatments and the monitoring thereof, have begun to be studied.\nA BM is a direct or indirect molecular indicator of abnormal joint tissue replacement, which corresponds to a normal component or a byproduct of the metabolic processes of the articular tissues.\nThe indirect BMs include cytokines and MMPs. Cytokines are proteins of cellular communication, secreted by the cells of the innate and adaptive immune system in response to the presence of different antigens. These cytokines mediate the physiological processes of immune cells and bone and cartilaginous tissues and stimulate different defensive and inflammatory responses, both at the local level (joint) or systemic. In articular diseases, tumour necrosis factor ? (TNF-?), interleukins 1 ? (IL-1 ?), 4 (IL-4) and 6 (IL-6), present in the synovial fluid, but at different levels in healthy animals and those who have clinical signs of OA, are considered of importance.The MMPs that have diagnostic value in OA are, fundamentally, the MMPs 2 and 9 which are proteases, zinc and calcium dependent, involved in physiological and pathological replacement of the MEC, degrading it in an OA processes. When there is a physiological bone turnover, the TNF-? and IL-1 ? released by chondrocytes, synovial cells and fibroblasts, produces a response of osteoblasts which increases the production of MMPs within a normal range. The expression of these enzymes is highly controlled by tissue inhibitors of metalloproteases (TIMs).\nThis thesis rises as a general hypothesis that, in horses, the modifications of the synovial fluid biological markers, in the initial or early stages of OA, precede the presentation of clinical and radiological signs. In addition, it is possible to observe biochemical changes in periods of remission of the disease.\nIts objectives are to:\n? Analyze the diagnostic value of synovial fluid molecular biomarkers as early predictors of clinical manifestation of osteoarthritis and in the monitoring of their evolution.\n? Determine if there is a temporal relationship between clinical diagnosis and synovial fluid biochemical analysis, in horses with and without clinical signs of OA.\n? Establish a clinical score that allows the diagnosis and monitoring of the evolution of the disease in its various phases.? To assess whether there is a relationship between the presence or absence of clinical signs and early biochemical changes in the synovial fluid.\nTo establish population clinical score values, 123 show jumping and Thoroughbred horses, aged between 1 and 28 years taken randomly were evaluated.From this initial group, three groups of animals were differentiated, according to their age category, to obtain reference values of cytokines and MMPs in order to characterize the profile of these biomarkers in the synovial fluid of healthy horses of different ages and horses with clinical signs of OA.The groups were: i) healthy foals between 1 and 2 years (n = 21), ii) healthy adults and with varied degrees of OA, aged between 3 and 14 years (n = 84) and iii) healthy adults over 15 years but with articular problems due to aging (n = 18).\nA general clinical examination and a particular one focused on the tarsal joint of both hind limbs were made, and synovial fluid was sampled from both tarsi. From these samples, IL-1 ?, IL-4, IL-6, TNF-?, MMPs 2 and 9, reactive protein C (RPC), total protein, albumin, and urea were determined.\nIn order to quantify the clinical examination of the joint, the following clinical score was developed:A) Score of lameness:0. No detectable.1. Difficult to observe and not always apparent (forced flexion pain).2. Difficult to observe on walking or trotting in straight line but apparent in certain circumstances of greater effort (work in circle).\n3. Always observable on trotting.- Sensitivity to palpation pressure (minor to major): 0 (-), 1 (+), 2 (++) and 3 (+++).- Forced flexion: 0 (-), 1 (+), 2 (++) and 3 (+++).\nB) Macroscopic analysis of synovial fluid- Visual appreciation of volume: 0. No fluid0.5. Scarce (- 2 ml)\n1. Intermediate (from 2 to 10 ml)1.5. Abundant (+ 10 ml)\n- Colour: 0. Transparent.\n0.4. Transparent whitish.\n0.8. Strong yellow.\n1.2. Blood stained.\n1.6. Reddish bleeding.\n2. Blood.-Turbidity: yes (1) / no (0)- Formation of 'thread' (stretch): 0.4: 5 cm.0.8: 3 cm.\n1.2: 1 cm.1.6: ClotC) Score of profile joint damage\n1. Normal.2. Increase of fluid.\n3. Slight hydrarthrosis.\n4. Severe hydrarthrosis with or without capsule fibrosis.\n5. Joint inflammation (increased size, pain, and heat).The proposed clinical score corresponds to a minimum of 2.3 points (no clinical manifestation) and a maximum of 20.1 points, considered of maximum severity.To assess the value of different levels of BMs in relation to the clinical score, we worked with the cytokines and MMPs reference values in synovial fluid previously set in our laboratory.\nResults from the measurement of cytokines (pg/ml) and MMPs (% of an internal control) were divided into 3 age categories, foals, adults and adults older than 15 years because results of the young animals (IL-1 ?: 120.96 ± 42.49 ª; IL-4; 6.10 ± 1.43 d, g; IL-6: 115.14 ± 52.49; TNF-?: 41.42 ± 13.64 ª; MMP-2: 140.47 ± 61.98 ª; MMP-9: 55.45 ± 58.17 ª, e) and adults older than 15 years (IL-1 ?: 57.12 ± 8.38; IL-4: 10.83 ± 4.20c; IL-6: 134.21 ± 45.24; TNF-?: 86.35 ± 43.25e; MMP-2: 49.13 ± 18.50; MMP-9: 8.28 ± 7.63) had a differential performance between them and the group of adults and adults, among them.\nIn the adult animals group, a clearly defined group distribution was observed in most of the variables studied in groups low (IL-1 ?: 37.37 ± 12.25 b; IL-4: 2.94 ± 0.93 ª, d; IL-6: 62.68 ± 25.16; TNF-?: 30.61 ± 6.39; MMP-2: 63.23± 25.61; MMP-9: 0.34 ± 0.15), medium (IL-1 ?: 61.75 ± 7.02; IL-4: 7.41 ± 0.71 d, g; IL-6: 148.66±28.86; TNF-?: 46.45 ± 10.94; MMP-2: 128.27±24.80 f;MMP-9: 11.19 ± 3.96) and high (IL-1 ?: 171.56± 132.68; IL-4: 14.61 ± 5.37 g; IL-6: 363.73± 123.06 e; TNF-?: 108.71 ± 50.39 e; MMP-2: 354.29± 174.88 e; MMP-9: 85.95 ± 47.97 e). However, the distribution of TNF-? and IL-1 ? in the three groups was not so marked, founding no significant differences between the average values of the low and medium group (a P < .001 vs. older adults; b P < .05 vs. High; c P < .01 vs. High; d P < .001 vs. High; e P < .001 vs. the other groups, f P < .05 vs. older adults; g P < .01 vs. older adults).IL-1 ? of healthy foals had a higher value that the rest of the other groups. The IL-1 ? average value of the foals group was overcome, albeit not significantly (p > 0.005), by the adults group with high values.\nFinally, using the proposed clinical score in 123 animals and associated with the results of the levels of cytokines and MMPs in the synovial fluid, the population was qualified in the following ranges or categories:\nGroup 1: Foals young horses between one and two years, with no clinical alterations of the joints, or variations of biomarkers due to OCD.\nGroup 2: Basal Equine adults with a clinical score no more than 4. Clinically healthy animals,without alterations in the articular inflammatory BMs or with slight alterations of them.\nGroup 3: Adult horses with a clinical score of 4-6 with mild clinical symptoms of OA.\n3a non active form with a decrease in IL-4 3b active form with several increased BMs.Group 4: Adult horses with a clinical score of 6-10 with OA symptoms and with or without changes in articular shape.4a non activate form with slight overall increase of BMS\n4b is active with rising 2 MMP, MMP9 expression and high IL-6 and other BMs.\nGroup 5: Elderly horses. Adults horses more than 15 years old. Chronic symptoms of OA by aging, with increases in some BMs and decreases in others, characteristic of the aging process.Once the response of different Cytokines and MMPs in OA cases was proved, in acute, remission or chronic stages, those results were correlated with the clinical score to validate it,and use it consistently in the clinical diagnosis of OA, at least in the tarsal locations (r2 = 0.65 for MMP-2 and r2 = 0.82 for MMP-9).\nApparently, the modification or elevation of cytokines and MMPs is an early sign that precedes the alteration of clinical index. On the other hand, in the different clinical categories different combinations were observed, being the decrease of IL-4 an incipient sign of disturbance in the articular environment. For example, in the 4b group, a characteristic profile, present in 30% of the animals, was characterized by a high IL-4 and IL-6 accompanied by high MMP 2. In the basal group and group 3b, with a 25% elevation in cytokines, an association of IL-1 ? and IL-6 high but with normal or decreased IL-4 and MMP 2 normal. And at higher scores more than 13, was very common to find the expression of MMP 9, absent in the Basal group and elevated MMP 2 values.\nThe follow-up of a patient with OA involves standardized semiologic techniques that can develop a fixed test, repeatable and with results validated by means of correlated complementary methods, such as arthroscopy, analysis of biomarkers, among others.\nTo achieve this goal, a score that covers most of the possible anamnesic and clinical observations must be achieved.In this experience, we have implemented a score using a combination of clinical scores, which received a numerical value whose sum resulted in a maximum score of 20.1 and a minimum cut of 2.3, whereas this value correspond to the clinical score of an animal without clinical alterations.\nApparently, the increased clinical score will result from the mechanical alteration that the articular disease produces. In general, the clinical score evolution of OA is a gradual process, with the exception of what happens in cases of acute arthritis, with an increase, as the physiological function of the cartilage and subchondral bone begins to be modify, as the active disease stays in time. And periods of remission as OA progresses are increasingly shorter.In the case of the elderly, were observed clinical scores higher than 7, no apparent signs of OA, only of aging, and in these cases the clinical score values were very difficult to roll back although the drop in the BMs.The indirect BMs of the cartilage metabolism, studied in this experience, were IL-1 ?, IL-4, IL-6, TNF-? and MMPs 2 and 9. IL-1 and TNF-? are released by the synovial membrane and articular chondrocytes with synovitis, product of the trauma. Both cytokines are released in excess and increase the rate of degradation of proteoglycan, decreases their synthesis or act together in both processes. This is partially accomplished by the release of MMPs and prostaglandin E2.IL-6 can be produced by articular chondrocytes and synovial fibroblasts, induced by the synthesis of IL-1 ? and TNF-?. At the same time, IL-6 stimulates at hepatic level acute phase protein synthesis, like RCP.\nIn clinical groups of higher scores, IL-4 increase to basal levels and even in some cases increases twice the basal, but associated with elevated levels of IL-6. On the other hand, it seems that elevated levels of biomarkers occur more regularly in the category of greatest clinical score and that, generally, they include older animals with higher chronic changes.\nPreliminary results obtained by our working group showed the absence of BMs in healthy animals or in periods of remission and its presence in animals with active OA. However, we have provided the knowledge that in animals with no clinical symptoms increased BMs act as an early indicator of future OA.\nThe TNF-? is the main mediator of the acute response that triggers the osteoarthritic process. The TNF-? increase occurs in the first moments of the inflammatory process, so it is very likely not found it in high levels in the synovial fluid. In our experience, the TNF? was found in little amount in horses both clinically healthy and in a non active phase of the OA. Therefore, its value lies in finding it present in elevated levels to confirm the acute inflammatory process.\nOn the contrary, the absence has no diagnostic value to determine the non-existence of the disease. At this point, it is also important to mention the relationship between TNF-? and IL-1 ? since the release of TNF-? cause an increase in the release of IL-1 ?, causing a greater activation of the previously described cell types for the release of MMPs.In active OA, IL-1 ? is elevated as it can be seen in animals in the sub "b" classification of the various categories of the clinical score presented in this thesis. At the same time, to reduce the release of MMPs, IL-6 should also been inhibit, because there is a redundant effect in which in\nthe absence of one, the other would carry out the same actions. Therefore if only one of the two it is inhibit, the enzyme activity would not be reduced.In clinically healthy horses, with high IL-6, since this pro-inflammatory cytokine, it could be considered that these animals were in a remission period or that it already existed a destruction of articular cartilage.\nMMPs 2 and 9 are increased in bone pathological process, surpassing the concentrations of TIMs. However, in these cases the MMP 2 presents values not as high as the MMP-9 and can be causing an homeostatic action, removing aged or abnormal cartilage. By other side, MMP 9 either it cannot be detected in normal joints or are in very low baseline, increasing significantly in cases of OA, septic slow-onset arthritis and rheumatoid arthritis in human beings. Therefore, according to this MMPs profile, it can be inferred that we are in front of a MMP-2-mediated normal remodelling processor or in front of an intense degradation the of cartilage with increased MMP 9 expression.\nIn our work, in clinically healthy animals we observed low levels of MMP-2 and absence of MMP-9. In animals with active OA, the MMP-2 significantly increased (p < 0.001) over the reference values of healthy horses. In horses in non active remission phase, the MMP-9 increased slightly and in horses in the chronic phase of the disease, the values were higher.\nIn conclusion, in horses who presented clinical symptoms compatible with OA, cytokines and BMs values and synovial fluid proteomic profiles were modified, while those free of symptoms, presented values compatible with normal joints. However, animals without clinical symptoms or subclinical showed alterations in the cytokines and MMPs profile of as an early sign of alteration of the intra-articular medium or as an indicator of a clinical remission stage. The clinical score presented high correlation with acute, chronic or recurrent biochemical modifications in OA horses or horses without the presence of the disease.\nTherefore, this score can be used in the clinical diagnosis of OA since the synovial BMs validated its evolution both positive and negative. In the same way, the BMs studied in this experience can be used as early complementary method in the detection, monitoring and therapeutic evolution of OA.\nKey Words: Osteoarthritis, diagnose, clinical score